Javanese Local Wisdom Memayu Hayuning Bawana in Al-Ghazali Perspective for Increasing Family Resilience - Arifah Pujiyanti; Ahman Ahman; Syamsu Yusuf; Pahri Siregar (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Globalization and technological developments are challenges in maintaining local wisdom and religious values. This study aims to explore the potential of Javanese community wisdom values, namely Memayu Hayuning Bawana (MHB) as a solution to increasing family resilience. In addition, MHB is also studied for its relevance to Islamic religious values through Al-Ghazali's perspective. The research method used is a mixed method with a Qual-quan sequential exploratory design. Quantitative analysis was conducted to determine the profile of family resilience, while qualitative analysis was used to examine the potential of MHB values as a solution to increasing family resilience and its relationship to Al-Ghazali's views. The study was conducted in Java, Indonesia, with 150 couples as participants. The results of the study found that the family resilience of Javanese society was 36.00% at a low level, 60.33% were in the medium category, and 3.67% were in the high category. In addition, the MBH values that can be used as a solution to increase family resilience are respecting each other's partners (Tepa Selira), pleasing the feelings of the partner (Karyenak tyasing sesama), being sincere in establishing a relationship (Sepi ing Pamrih, lan Rame ing Gawe), and being careful in acting (Eling lan Waspada). These values are in accordance with Al-Ghazali's perspective on the criteria for the nature of a partner. The characteristics of Al-Annanah, Al-Mananah, Al-Haddaqah, Al-Syaddaqah, Al-Barraqah, and Al-Hananah need to be avoided and are contrary to the MBH values and Al-Ghazali's perspective. Thus, the value of maintaining MBH can create a family that is orderly (tata), calm (titi), and peaceful (tentrem) or in Islamic literature it is called sakinah, mawadah, warahmah. Globalisasi dan perkembangan teknologi merupakan tantangan dalam pemertahanan nilai kearifan lokal dan religi. Penelitian ini bertujuan untuk menggali potensi nilai kearifan masyarakan Jawa yakni Memayu Hayuning Bawana (MHB) dalam sebagai solusi peningkatan ketahanan keluarga. Selain itu, MHB juga dikaji relevansinya nilai religi Islam melalui pespektif Al-Ghazali. Metode penelitian yang digunakan adalah mixed method dengan desain eksploratori sekuensial Qual-quan. Analisis kuantitatif dilakukan untuk mengetahu profil ketahanan keluarga, sedangkan kualitatif untuk mengkaji potensi nilai MHB sebagai solusi peningkatan ketahanan keluarga dan kaitannya dengan pandangan Al-Ghazali. Penelitian dilakukan di Jawa, Indonesia, dengan jumlah partisipan sebanyak 150 pasang suami istri. Hasil penelitian menemukan bahwa ketahanan keluarga masyarakat Jawa yakni 36,00% berada dalam level rendah, 60,33% berada pada kategori sedang, dan 3,67% berada pada kategori tinggi. Selain itu nilai MBH yang dapat dijadikan solusi meningkatan ketahanan keluarga yakni saling menghargai pasangan (Tepa Selira), menyenangkan perasaan pasangan (Karyenak tyasing sesama), tulus ikhlas dalam menjalin hubungan (Sepi ing Pamrih, dan Rame ing Gawe), serta berhati-hati dalam bertindak (Eling lan Waspada). Nilai tersebut sesuai dengan perspektif Al-Ghazali mengenai kriteria sifat pasangan. Sifat Al-Annanah, Al-Mananah, Al-Haddaqah, Al-Syaddaqah, Al-Barraqah dan Al-Hananah perlu dihindari dan bertentangan dengan nilai MBH dan perspektif Al-Ghazali. Dengan demikian, nilai pemertahanan MBH dapat mewujudkan keluarga yang teratur (tata), tenang (titi), dan tentram (tentrem) atau dalam literatur Islam disebut sakinah, mawadah, warahmah.